Effectiveness of nursing intervention for increasing hope in patients with cancer: a meta-analysis - Ping Li; Yu-Jie Guo; Qing Tang; Lei Yang (Universidade de São Paulo, 2018)
ABSTRACT Objective: to evaluate the efficacy of nursing interventions to increase the level of hope in cancer patients, in a meta-analysis. Methods: electronic databases were searched. Two of the authors independently extracted data from the eligible studies, and Stata 13.0 software was used to pool the data. Results: nine randomized controlled trials were included, and methodological quality of each randomized controlled trial (RCT) was evaluated using Cochrane handbook recommendations. A random effects model was used to combine results from eligible studies. The pooled results using the fixed effects model showed that scores to first effects increase significantly after the use of nursing intervention between the groups. Heterogeneity was observed among the studies for posttest (df = 8, P = 0.000; I2 =76.1 %). The results indicated significant heterogeneity across the nine selected studies. The test for heterogeneity showed no homogeneity among studies for follow-up (df = 8, P = 0.328; I2 = 12.9 %), and there was no statistical significance. Conclusion: the current evidence suggests that nursing intervention has a positive effect on hope in cancer patients. However, more large-scale and high-quality randomized controlled trials are needed to confirm these results.